2012
DOI: 10.1007/s10120-012-0163-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer treated in 2002 in Japan: 2009 annual report of the JGCA nationwide registry

Abstract: BackgroundThe Japanese Gastric Cancer Association (JGCA) started a new nationwide gastric cancer registration in 2008.MethodsFrom 208 participating hospitals, 53 items including surgical procedures, pathological diagnosis, and survival outcomes of 13,626 patients with primary gastric cancer treated in 2002 were collected retrospectively. Data were entered into the JGCA database according to the JGCA classification (13th edition) and UICC TNM classification (5th edition) using an electronic data collecting syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
274
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(291 citation statements)
references
References 3 publications
5
274
1
4
Order By: Relevance
“…According to the JGCA data, cumulative 5-year survival of stage IV patients was 15.3%, 2 and Korean data also showed similar results with 18%. 3 Moreover, among all stage IV patients, 4% to 9% of them are said to be too advanced with no chance of curative surgery and their prognosis is absolutely poor showing less than 10% at 3 years after diagnosis.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…According to the JGCA data, cumulative 5-year survival of stage IV patients was 15.3%, 2 and Korean data also showed similar results with 18%. 3 Moreover, among all stage IV patients, 4% to 9% of them are said to be too advanced with no chance of curative surgery and their prognosis is absolutely poor showing less than 10% at 3 years after diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…2 Therefore, we do not have a particular treatment algorithm against stage IV patients at this time. However, we weigh patients' clinical symptoms for decision making.…”
Section: Methodsmentioning
confidence: 99%
“…The 5‐year survival for patients with liver metastasis was 11.4% in Japanese GC patients 35. The median survival times of 3‐4 months after detection of bone metastasis have been reported in some studies36, 37 and the median survival after treatment of brain metastasis was about 3 months 23.…”
Section: Discussionmentioning
confidence: 93%
“…Albeit recent advancements in surgical techniques and perioperative care, the postoperative morbidity rate is as high as approximately 40% after esophageal cancer surgery,1, 2 and 20–30% after both gastric cancer surgery3, 4, 5 and colorectal surgery 6, 7, 8. Various reports have shown that such postoperative complications frequently reduce the overall survival (OS) as well as cancer‐specific survival after major surgery for cancer 9.…”
Section: Introductionmentioning
confidence: 99%